2013
DOI: 10.1111/aap.12003
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol inhibits the contractility of isolated human myometrium

Abstract: This study was conducted to determine whether the atypical opioid analgesic tramadol inhibits the contractility of isolated non-pregnant human myometrium. Ten strips of non-pregnant human myometrium stimulated with 55 mm potassium chloride (KCl) were treated with three concentrations (30, 100 and 300 μm) of tramadol to test for any inhibitory effect of tramadol. The effects of concurrent administration of the ß adrenoceptor antagonist propranolol (1 μm), the guanylyl cyclase and nitric oxide synthase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Tramadol is a synthetically produced opioid with a specific chemical formula; C16- H25- NO2 (Carrillo-Munguía et al 2015 ; Shah et al 2013 ; Matthiesen et al 1998 ). Tramadol is an analgesic drug with a mechanism of action influencing pain sensation pathways (Mohamed et al 2015 ; Shah et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tramadol is a synthetically produced opioid with a specific chemical formula; C16- H25- NO2 (Carrillo-Munguía et al 2015 ; Shah et al 2013 ; Matthiesen et al 1998 ). Tramadol is an analgesic drug with a mechanism of action influencing pain sensation pathways (Mohamed et al 2015 ; Shah et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol is a synthetically produced opioid with a specific chemical formula; C16- H25- NO2 (Carrillo-Munguía et al 2015 ; Shah et al 2013 ; Matthiesen et al 1998 ). Tramadol is an analgesic drug with a mechanism of action influencing pain sensation pathways (Mohamed et al 2015 ; Shah et al 2013 ). This drug is used for the prevention and treatment of moderate to severe pains (Abdel-Zaher et al 2011 ; Elkhateeb et al 2015 ; Matthiesen et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Where this result in agreement with previous studies, which reported weight loss, decrease of testosterone due to facilitating the damage of spermatogenic cells via increase of reactive species. The deficiency of testosterone would add in producing immature sperm [29].…”
Section: Discussionmentioning
confidence: 99%
“…55 mM KCl is the standard concentration of KCl used in our laboratory for stimulating the contraction of the isolated myometrium. [ 13 14 ] We have found this concentration of KCl to be suitable because it is effective and can be washed out easily following muscular contraction. Then 55 mM KCl was administered again.…”
Section: Methodsmentioning
confidence: 99%
“…Contractility was quantified by the maximum height of contraction and the area under the contractile curve (AUCC), a method which has been standardized in our laboratory. [ 13 14 ] These parameters were determined by scanning the tracings after each experiment and analysis with the software Image Tool (University of Texas Health Sciences Center at San Antanio, TX, USA). This was done by comparing statistically the values of these parameters of the control data (after the administration of KCl alone) and the values of the test data (after the administration of the test drug (s) with KCl).…”
Section: Methodsmentioning
confidence: 99%